Harmonization of Constitutional Morality and Public Morality - Munish Swaroop; Gurudev Sahil (AG Volumes, 2026)
This chapter will explore the intricate relationship between “public morality” and “constitutional morality” within the context of religious freedom in India. It will examine how the Constitution of India, particularly Articles 25 and 26, will address the interplay between these two concepts. The chapter will delve into the definitions and implications of “public morality” and “constitutional morality,” highlighting their complex interpretations by courts. The chapter will also underscore the evolving nature of public morality and its interactions with religious practices under Article 25 and 26. It will discuss cases such as Govt. of NCT of Delhi v. Union of India and Navtej Singh Johar v. Union of India to elucidate the application of constitutional morality in by the Indian Judiciary. Ultimately, it will reflect on the challenge of determining precedence between public and constitutional morality and will look into the veering towards their alignment consequently a harmonious balance between the two may be forged over time through the continued judicial interpretation.